Dispersion Theory of Polaron in a Parabolic Quantum Dot at Finite Temperatures - 孙尔林 冯东海 贾天卿 周侃 孙真荣 (Communications in theoretical physics, 2011)
By using the dispersion theory instead of the Frohlich Hamiltonian, the polaron energy in a quantum aot with a parabolic confinement potential is investigated at finite temperatures. It is found that the self-trapping energy of the polaron decreases with the increasing temperature, and the temperature effect is more obvious in quantum dots with weaker confinement.